TINDAK PIDANA PRAKTIK KEDOKTERAN TANPA IZIN PRAKTIK - Winda Ayu Setyowati; Norbert Tanto Harjadi (Reformasi Hukum Trisakti, 2023)
A medical crime is a criminal act that violates medical ethics. Heny Desrityani engaged in fraudulent behavior, letter forgery, and illegal drug use. The question posed in this study is whether the defendant's activities are compliant with Articles 77 and 78 of Law No. 29 of 2004 and what other crimes the defendant may have committed. This research methodology was discovered through a literature review, and descriptive analysis was the type of research that was being done. The defendant used a doctor's degree and medical equipment and methods to commit a medical crime, according to the findings of the investigation and discussion. The defendant also committed fraud and letter forgery. Which resulted in the conclusion that the defendant was only subject to one article because there was the principle of Lex Specialis Derogat Legi Generali and in this case the sentence imposed was relatively light and not in accordance with the objectives of the existing punishment.